الهدف الديني للاستشراق من دراسة التراث الإسلامي من وجهة نظر محمد البهي ومحمد ياسين عريبي - Yusuf Musa Ali Abdullah Abu Aliqah,; Abdull Rahman Mahmood,; Mohd Nasir Omar,; Idris Zakaria, (Universiti Kebangsaan Malaysia, 2012)
The West follows a number of methods and targets to destroy the Islamic world and to impose its culture on the reality of the Arab Islamists. Whether it is forcibly by direct colonialism, orientalism or by national elite, which is taught in the West and inspired by its exemplar and returns to its loyal carrier. It fights and contests the authenticity of Islam and its concept. Building upon it is also the research problem lying in the incitement towards the aggressive curriculum accompanied by the colonial schools in orientalism, which has put itself in the holistic civilization draft, but it comes by the central European framework which is based on the principle of eligibility and approval of Europeans only in urbanization and progress. Denying this vulnerability on others, so comes about the importance of research, as a renewal and stereotyping for many topics which develops the knowledge in the distinguished and the importance upon the education, culture, and ideology curricula in the Islamic world. As for the goal; it is possible to master a generation of researchers who moved out the wrong citizens, counterfeiting and fraud which takes place in orientalism, intentionally or un-intentionally because in its defamation is the foundations and principles of Islamic thought, their compliance to the curricula is offensive towards the Islamic ideology and it is not possible to apply it onto Islamic principles.